High‐resolution anorectal manometry and dynamic pelvic magnetic resonance imaging are complementary technologies. Issue 1 (January 2015) - Jodorkovsky, Daniela; Macura, Katarzyna J; Gearhart, Susan L; Dunbar, Kerry B; Stein, Ellen M; Clarke, John O
Abstract Background and Aim Dynamic pelvic magnetic resonance imaging (DP‐MRI) offers a comprehensive evaluation of pelvic organ structure in addition to functional information regarding evacuation. Opportunity to apply this technology can be limited due to regional lack of availability. Ideally, clues from standard anorectal testing could predict abnormalities on DP‐MRI, leading to its efficient use. The aim of this study is to determine whether high‐resolution anorectal manometry (HR‐ARM) correlates with findings on DP‐MRI. Methods This is a retrospective study of HR‐ARM performed on patients with constipation who also underwent DP‐MRI. Studies were reviewed for significant findings including posterior pelvic organ prolapse, rectocele > 3 cm, rectal intussusception, and anorectal angle. Statistical analysis was performed using Pearson's correlation coefficient, Student's t‐test, and Fisher's exact test. Results Twenty‐three patients undergoing HR‐ARM (age range 25–78) also underwent DP‐MRI. All were female; 76% were Caucasian. Twenty had significant structural findings: small pelvic prolapse (n = 2), moderate pelvic prolapse (n = 10), large pelvic prolapse (n = 9), rectocele (n = 8), or rectal intussusception (n = 3). Only intrarectal pressure on HR‐ARM weakly correlated with size of rectocele (r = 0.46; P = 0.03) and degree of pelvic organ prolapse (r = 0.48; P = 0.02). The remainder of the HR‐ARM parameters did not significantly correlate with DP‐MRI findings. Patients with dyssynergy were not more likely to have rectoceles > 3 cm (44.4% versus 35.7%; P = 0.5) or large prolapses (44.4% versus 50%, P = 1.0), compared with those without dyssynergy, on HR‐ARM. Conclusion We were unable to find a correlation between HR‐ARM findings and structural pelvic defects on DP‐MRI. Therefore, these two technologies provide complementary information in the evaluation of defecatory dysfunction.